Air/Water Interfacial Formation of Freestanding, Stimuli‐Responsive, Self‐Healing Catecholamine Janus‐Faced Microfilms. (15th September 2014) - Hong, Seonki; Schaber, Clemens F.; Dening, Kirstin; Appel, Esther; Gorb, Stanislav N.; Lee, Haeshin
<x xml:space="preserve">Abstract</x> A catecholamine freestanding film is discovered to be spontaneously formed at the air–water interface, and the film has unique properties of robust surface adhesiveness, self‐healing, and stimuli‐responsive properties. The interfacial film‐producing procedure is a simple single step containing polyamines and catechol(amine)s. It is found that oxygen‐rich regions existing at an air–water interface greatly accelerate the catecholamine crosslinking reaction. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>